2015
DOI: 10.4187/respcare.03551
|View full text |Cite
|
Sign up to set email alerts
|

Assessing New Technologies in Aerosol Medicine: Strengths and Limitations

Abstract: Aerosols are the mainstay of treatment for pulmonary diseases such as asthma, cystic fibrosis, and COPD. In addition, aerosols are also being used for systemic drug delivery. Patients need devices that are safe, reliable, portable, and easy to use; have few steps in their operation; help them keep track of the remaining doses; are not expensive; and provide age-appropriate positive reinforcement and feedback. Computational fluid dynamics, human factor sciences, and quality by design are now applied to device d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“… 29 The choice of therapy, however, ultimately depends on a wide range of factors, including the prescribing physician, the availability of specific drug/device pairings, drug cost, and patient preferences and satisfaction. 3 , 22 , 26 , 28 , 30 , 31 Each of the delivery devices that are available for administering drugs to patients with COPD (eg, pMDIs, DPIs, SMIs, and nebulizers) has advantages and disadvantages ( Table 2 ). 3 , 6 , 29 , 31 , 32…”
Section: Pharmacologic Therapymentioning
confidence: 99%
“… 29 The choice of therapy, however, ultimately depends on a wide range of factors, including the prescribing physician, the availability of specific drug/device pairings, drug cost, and patient preferences and satisfaction. 3 , 22 , 26 , 28 , 30 , 31 Each of the delivery devices that are available for administering drugs to patients with COPD (eg, pMDIs, DPIs, SMIs, and nebulizers) has advantages and disadvantages ( Table 2 ). 3 , 6 , 29 , 31 , 32…”
Section: Pharmacologic Therapymentioning
confidence: 99%
“…Beyond the assessment of function, CFD can play an important role in understanding deposition patterns of inhaled medication. In particular, CFD can indicate the key drivers for deposition by taking into account inhaler device, inhalation profile, aerosol characteristics, and a patient's diseased airway geometry, providing the potential for tailoring treatment to an individual . By better understanding the role each variable plays in drug exposure, more personalized drugs and devices can be developed by investing resources in areas that have the greatest impact on drug delivery thereby reducing the probability of having chronically undertreated areas in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…The main applications for these types of simulations are to understand the dispersion and level of penetration into the lung of inhaled pharmaceutical products. Several in depth reviews have been written on this topic (i.e., Refs ) and we will not discuss this area in any depth in the current review, however, this topic is mentioned in the key CFD application sections below.…”
Section: What Can Computational Fluid Dynamics Offer Over Existing Mementioning
confidence: 99%
“…Melani 8 concluded that changing the inhaler device would not be as effective as providing repeated health-care training for these devices. In addition, Berlinski 23 emphasized that providing a proper education to both health-care professionals and patients is critical to improving patient adherence.…”
Section: Discussionmentioning
confidence: 99%